2012
DOI: 10.1016/j.jsps.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of levetiracetam in pediatric epilepsy

Abstract: Our results confirm that LEV may be an effective adjunctive therapy in treatment of childhood epilepsy, especially tonic-clonic seizure, with possible no evident side effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…[ 2 ] In a study of 6–12-year-old children with partial seizures treated with levetiracetam, 45% of them had complete improvement after 7–12 months of follow-up. [ 21 ] In a case series of three children with BCECTS treated with levetiracetam, only one child experienced one seizure; otherwise, all the children were seizure-free. [ 1 ] This study achieved comparable results, in which all cases were seizure-free after six months.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In a study of 6–12-year-old children with partial seizures treated with levetiracetam, 45% of them had complete improvement after 7–12 months of follow-up. [ 21 ] In a case series of three children with BCECTS treated with levetiracetam, only one child experienced one seizure; otherwise, all the children were seizure-free. [ 1 ] This study achieved comparable results, in which all cases were seizure-free after six months.…”
Section: Discussionmentioning
confidence: 99%
“…Elberry and Associates conducted a study and found that generalized tonic-clonic (59%) and tonic seizure (27%) were the major seizure types when they studied 22 patients. 22 It is quite evident from the results that it took near about 7 months to 1 year for the patients (45%) to become seizure free. Normalized EEG was observed in patients (80%) out of 10 patients.…”
Section: Discussionmentioning
confidence: 91%
“…Epilepsy is one of the most widespread noninfectious diseases worldwide and one of the most common dangerous neurological disorders [3][4][5][6][7][8][9]. The highest rate of epilepsy is in the first year of life and decreases to the adult levels at ten years old [10,11].…”
Section: Pharmacovigilancementioning
confidence: 99%